Lessons from an aborted second-generation rent control in Catalonia - Konstantin A. Kholodilin; Fernando A. López; David Rey; Pelayo Gonzalez Arbues (Deutsches Institut für Wirtschaftsforschung (DIW), 2022)
This study investigates the effects of short-lived rent control regulations introduced in Catalonia in September 2020 and revoked in March 2022. Using the microdata of the largest Spanish housing advertisement portal idealista between January 2017 and May 2022, we analyze the dynamics of prices and supply for dwellings offered for rent and for sale. We also examine separately the rental and sales markets. We find that the introduction of rent control led to a reduction in rents in both controlled and uncontrolled Catalan municipalities, while quantities virtually did not react to it. The selling prices of dwellings remained unchanged, whereas their supply increased substantially. The revocation of rent control caused a strong increase in the rental and selling prices in all municipalities, no increase in the supply, with the exception of the supply of regulated dwellings for sale. In addition, using the macrodata on housing construction we find that during the rent-control period the average number of monthly dwelling starts in Catalonia declined by 6% compared to January 2019 - September 2020, while nationwide it increased by almost 12%. Thus, the effects are broadly consistent with the predictions of the economic literature on rent controls.
Keywords: C43; O18; R38; 330; rent control; Catalonia; asking rents; asking selling prices